FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN PADA PT. ASTRA CABANG MEDAN - Nainggolan, Melisa G; Ritonga, Sinar (UNIKA Santo Thomas, 2012)
The purpose of this study is to investigate and analyze the dominant factor influencing job satisfaction of employees at PT Astra Branch Medan. The study population was all employees of PT Astra Branch Medan in 2012 as many as 132 people. Samples were taken as many as 105 people. Data collection techniques used were questionnaires and documentation techniques. To analyze the data used factor analysis. From the results of research and discussion shows that the dominant factor influencing job satisfaction of employees of PT Astra Branch Medan is an incentive or bonus, employment policies and procedures, promotion, intrinsic of employment, social security and service vehicles. The most dominant factor influencing job satisfaction is an incentive or bonus. Advice given to the leadership of the company is to increase employee job satisfaction, companies should add big incentives or bonuses, pay attention to the determination of employment policies and procedures, maintain the social security administration and service vehicles. Companies should provide the greatest opportunities for the best performing employees to be promoted to a higher position.